Women’s Empowerment in Informal Settlements: The Case of Manohara, Kathmandu - Acharya, Bala Ram (Nepalese Journal of Society and Culture, 2025)
This study investigates the condition of women’s empowerment in Kathmandu’s Manohara squatter settlement. It examines how women’s access to resources and wellbeing are influenced by poverty, low levels of education and traditional gender roles. Sen’s capability approach and a socialist feminist perspective are used in the study to investigate the level of empowerment development of women. Basic descriptive statistics, unstructured interviews for the interpretation of data and field observations were all used simultaneously. Data was collected from 48 targeted households. The findings of this research indicate that poverty and patriarchal social structure are causes of marginalization for women in the Manohara squatter. They were unable to obtain formal education and employment properly because of economic and social exclusion and poverty. Despite increased income and education in a few cases, a significant respondent’s level of empowerment is still negligible. This study shows that having time, freedom, self-respect and social recognition are also important in the community and at home equally to empower women. The study suggests to understand comprehensive nature of empowerment through interpretative research. It indicates that disempowerment of women in the study area is influenced by both external and internal factors. Material and nonmaterial aspects are equally important. State, development organizations involved in women’s empowerment and family support systems promote equal gender status.